Anchoring the landscape: human utilization of the Cerro Gavilán 2 rockshelter, Middle Orinoco, from the Early Holocene to the present - Scaramelli,Kay (2017)
Abstract Initial archaeological investigations at Cerro Gavilán 2, a rockshelter located in the Bolívar State of Venezuela, reveal evidence for human activity that spans the Early Holocene to the present. This report summarizes the information obtained through surface collection, limited excavation, and documentation of the surface features and rock art in the cave. Accelerator mass spectrometry (AMS) 14C analysis established dates from excavated strata that range between 9250 ± 60 BP to 3440 ± 40 BP, and are associated with a unifacial flake technology and charred faunal and floral remains, whereas surface remains span the known ceramic sequence for the area. Rock art corresponds to distinctive superimposed styles that indicate continual repainting of the cave through time, serving to anchor the site to the landscape for multiple societies inhabiting the region. It is suggested that the shelter may have fulfilled different functions over time and a sequence of seasonal residential, ritual, and funerary activities is proposed. The rich cultural context found in Cerro Gavilán 2 contributes to advances in Amazonian archaeology that are redefining our knowledge of early developments and the complexity of human/environmental interactions in tropical America.